INTERNATIONAL CIVIL ADMINISTRATION AND STATE BUILDING PROCESS IN KOSOVO - Nurboja, Reshat (European Scientific Journal, ESJ, 2015)
Based on UN Security Council Resolution 1244 adopted on June 10, 1999 Kosovo was put under the international civil administration named UNMIK (UN mission in Kosovo). During the several years UNMIK exercised its powers in Kosovo based on four established pillars. A lots of debates were developed within the academic world about the role of UNMIK in Kosovo, its functions and especially the role it played for the process of the state building in Kosovo. A series of question were raise permanently about whether this mission was only a civil administration or it was a modern type of protectorate. Of course there were also other discussions developed regarding the UNMIK issue in Kosovo. The paper intends to explain the UNMIK mission and its legal basis with the special emphasizes the role it played in the process of Kosovo independence and the state building process. Some claim that UNMIK had a symbolic role in the process of state building whereas it had no role at all in the process of Kosovo independence. Paper analyses the entire process of UNMIK and comes up with findings as well as with the recommendations these types of international administrations should take into the consideration in the future if the need appears.